Optimal stockpiling policies for resource-dependent economies - Axel Behrens (Kiel Institute of World Economics (IfW); ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 1990)
In this paper we derive optimal stockpiling policies for an economy that faces an embargo threat with respect to essential resources. The properties of the optimal program depend crucially on the access of this country to a perfect capital market and on the factor allocation in embargo periods. This paper is similar to Bergstrom/Loury/Persson (1985) but in contrast to them focuses on the relationship of stockpiling to domestically produced resources and on the use of these resources as an input in production.
Keywords: 330; Vorratswirtschaft; Ressourcenökonomik; Außenhandelsbeschränkung; Theorie